Economic Evaluation of Boceprevir for the Treatment of Patients with Genotype 1 Chronic Hepatitis C Virus Infection in Hungary - Raymond Odhiambo; Jagpreet Chhatwal; Shannon Allen Ferrante; Antoine El Khoury; Elamin Elbasha (Journal of Health Economics and Outcomes Research)
**Background:** Recent international, randomized, placebo-controlled clinical trials (SPRINT-2; RESPOND-2) demonstrated that the triple combination of peginterferon (PEG), ribavirin (RBV) and boceprevir (BOC) was more efficacious than the standard dual therapy of PEG and RBV in treatment of patients chronically infected with genotype 1 hepatitis C virus (HCV) infection. The objective of this study was to evaluate the cost-effectiveness of triple therapy in both treatment-naive and treatment-experienced patients in Hungary.